Pulse interactions in weakly nonlinear coherent optical communication links. Issue 1 (April 2021) - Gibney, J; Kuk, I A; Gabitov, I R
Abstract: The intrachannel interaction of pulses in weakly nonlinear coherent optical fiber lines is theoretically investigated. It is shown that the main contribution to the perturbation of the optical field comes from resonant interactions of ordered triplets of pulses. The structure of triplets is determined. The weight contributions of such interactions are calculated. A classification of interactions using Löschian numbers is proposed. Using computer simulation, the dependence of the average energy of the optical field perturbations on the distance is shown. Based on the performed analysis, an effective algorithm is proposed for assessing the perturbations resulting from intrachannel interaction.